The effectiveness of perceived social support in discount stores in Korea. Issue 4 (24th July 2020) - Song, Chanho; Brown, Haakon T.; Tameez, Rahmatullah Rami
Abstract : Purpose: The purpose of this study is to bridge the gap in literature to examine social support that customers receive from their relationships with frontline service providers in discount stores. Design/methodology/approach: In total, 381 consumers are accessed through an online survey administered by an online research company in South Korea. The authors use the structural equation model (SEM) technique to test the proposed hypotheses. Findings: Social support (emotional, instrumental, informational and appraisal) significantly influences customer satisfaction in discount stores. In addition, customer satisfaction significantly influences word of mouth (WOM) and purchase intention. Originality/value: Very few studies have addressed the relationship between social support and consumer satisfaction in the discount store industry. This research helps to understand that social support is a basic consideration for customers of discount stores when they are shopping.